(untitled) (Nonconventional Technologies Review, 2021)
The Nonconventional Technologies Review is a scientific engineering publication of the Romanian Association for Nonconventional Technologies, which has started in 1997, with trimestrial appearance. The publication is addressed to all engineers and scientists interested in nonconventional technologies.